DAMPAK PROGRAM GARUDA MILES TERHADAP LOYALITAS PELANGGAN PT GARUDA INDONESIA - Vica Harahap; Safira Safira; Charles AN (Institut Transportasi dan Logistik Trisakti, 2017)
This study aims to find out the effect of Garuda Miles Program to the customers’ loyalty. The research was using hypothesis testing. The method used was a simple linear regression analysis with a total sample of 30 people. The result of the research shows that the effect of Garuda Miles Program to the customers’ loyalty with regression equation y is 6.86 + 0.8x. The Garuda Miles Program has a very strong and positive influence on customers’ loyalty shown by r = 0.81. Customers’ loyalty has been affected by Garuda Miles program of 65.61% (coefficient determination), while the remaining 35.39% is determined by other factors. The result of the hypothesis test is t –count > t-table (12.59> 2,048). Therefore, there is a significant influence of Garuda Miles Program to the customers’ loyalty.